x/5+y/3 = 2/15
2(x-3) +3 (y-2)=-12
Soluções para a tarefa
Respondido por
7
2 ( x - 3 ) + 3 ( y - 2 ) = -12
2 x - 6 + 3 y - 6 = - 12
2 x + 3 y = - 12 + 12
2 x + 3 y = 0
2 x = - 3 y
x = - 3 y / 2
x = - 1,5 y
x / 5 + y / 3 = 2 / 15
(- 1,5 y / 5) + y / 3 = 2 / 15
- 1,5 y / 5 = 2 / 15 - y / 3
mmc de 3 e 15 = 15
- 1,5 y / 5 = 2 - 5 y / 15
- 1,5 y = 2 - 5 y / 15 . 5
- 1,5 y = 10 - 25 y / 15
- 1,5 y + (25 y / 15) = 10 / 15
- 1,5 y + 25 y = (10/ 15) . 15
23,5 y = 150/ 15
23,5 y = 10
y = 10 / 23,5
y = 0,42
x = - 1,5 y
x = - 1,5 . 0,42
x = - 0,63
2 x - 6 + 3 y - 6 = - 12
2 x + 3 y = - 12 + 12
2 x + 3 y = 0
2 x = - 3 y
x = - 3 y / 2
x = - 1,5 y
x / 5 + y / 3 = 2 / 15
(- 1,5 y / 5) + y / 3 = 2 / 15
- 1,5 y / 5 = 2 / 15 - y / 3
mmc de 3 e 15 = 15
- 1,5 y / 5 = 2 - 5 y / 15
- 1,5 y = 2 - 5 y / 15 . 5
- 1,5 y = 10 - 25 y / 15
- 1,5 y + (25 y / 15) = 10 / 15
- 1,5 y + 25 y = (10/ 15) . 15
23,5 y = 150/ 15
23,5 y = 10
y = 10 / 23,5
y = 0,42
x = - 1,5 y
x = - 1,5 . 0,42
x = - 0,63
Perguntas interessantes
Matemática,
9 meses atrás
Psicologia,
9 meses atrás
Química,
9 meses atrás
Matemática,
1 ano atrás
Informática,
1 ano atrás
Administração,
1 ano atrás